Advances in TENGs for Marine Energy Harvesting and In Situ Electrochemistry - Zhang, Chuguo; Hao, Yijun; Lu, Xiangqian; Su, Wei; Zhang, Hongke; Wang, Zhong Lin; Li, Xiuhan (Nano-Micro Letters, 2025)
The large-scale use of ample marine energy will be one of the most important ways for human to achieve sustainable development through carbon neutral development plans. As a burgeoning technological method for electromechanical conversion, triboelectric nanogenerator (TENG) has significant advantages in marine energy for its low weight, cost-effectiveness, and high efficiency in low-frequency range. It can realize the efficient and economical harvesting of low-frequency blue energy by constructing the floating marine energy harvesting TENG. This paper firstly introduces the power transfer process and structural composition of TENG for marine energy harvesting in detail. In addition, the latest research works of TENG on marine energy harvesting in basic research and structural design are systematically reviewed by category. Finally, the advanced research progress in the power take-off types and engineering study of TENG with the marine energy are comprehensively generalized. Importantly, the challenges and problems faced by TENG in marine energy and in situ electrochemical application are summarized and the corresponding prospects and suggestions are proposed for the subsequent development direction and prospects to look forward to promoting the commercialization process of this field. Highlights: 1 The basic information of triboelectric nanogenerator (TENG), the power conversion process, and key points of the marine energy harvesting TENGs was introduced in detail. 2 An in-depth introduction and analysis of relevant research with the marine energy harvesting were conducted through gradient classification. 3 This review not only provided a deeper summary of the latest research progress, discoveries, and challenges, but also made a rational outlook on solutions to related issues and future development directions.